Unlocking environmental archives in the Arctic—insights from modern diatom-environment relationships in lakes and ponds across Greenland - Weckström, Kaarina; Weckström, Jan; Wischnewski, Juliane; Davidson, Thomas A.; Lauridsen, Torben L.; Landkildehus, Frank; Christoffersen, Kirsten S.; Jeppesen, Erik (Frontiers in Ecology and Evolution, 2023)
Given the current rate of Arctic warming, the associated ecological changes need to be put into a longer-term context of natural variability. Palaeolimnology offers tools to explore archives stored in the sediments of Arctic lakes and ponds. The interpretation of these archives requires a sound knowledge of the ecology and distribution of the sedimentary proxy organisms used. Here we explored the relationship between diatoms, a widely used proxy group of siliceous algae, and the environmental drivers defining their assemblages and diversity in 115 lakes and ponds in Greenland, a markedly understudied arctic region covering extensive climate and environmental gradients. The main environmental drivers of diatom communities were related to climate and lake ontogeny, including both measured and unmeasured (spatially structured) environmental variables. The lakes and ponds in the northern study regions showed a distinctive dominance of small benthic fragilarioid species, while diatom communities in the South(west) of Greenland were more varied, including many epiphytes, owing to the longer growing season and higher habitat diversity of these lakes and ponds. The newly established lakes in the Ilulissat region host markedly different communities compared to all other sites. Species diversity followed an overall clear latitudinal decline towards the North. Despite the large distances between our study regions, diatom dispersal appeared not to be limited. Based on our results, diatoms are an excellent proxy for climate-mediated lake ecosystem change in the Arctic and thus a valuable tool for climate reconstructions in the region. Particular consideration should be given to often unmeasured climate-related drivers, such as in-lake habitat availability, due to their apparent importance in defining Arctic diatom communities.